Latitudinal Beta‐Diversity Gradient of Riverine Macroinvertebrate: Interplays of Climatic and Land Use Factors - Ruxia Qiao; Hanrui Wang; Yuqing Lin; Qiuwen Chen; Jianyun Zhang; Kai Chen; Tao Feng; Shufeng He; Hanlu Yan (Global Ecology and Biogeography, 2025)
Aim Climate change and land use have major effects on macroinvertebrate biodiversity, but it is unclear how they shape spatial variations, particularly at large scales. This study explored the latitudinal patterns of beta diversity in riverine macroinvertebrate assemblages and examined how they are shaped by climate and land use. Location China (18°–48° N). Time Period From 2006 and 2021. Major Taxa Studied Riverine macroinvertebrates. Method A comprehensive dataset covering macroinvertebrate taxa from 42 watersheds across China was compiled to explore the latitudinal patterns of taxonomic, functional, and phylogenetic beta diversities, including turnover and nestedness components. Generalised additive models were used to assess the impacts of climatic and land use variables, selected from 20 climatic and 10 land use candidates, on latitudinal patterns of beta diversity. Results Taxonomic and functional beta diversities shared a non‐monotonic latitudinal pattern, minimised at 24°–30° N, contrasting with the monotonic increase in phylogenetic beta diversity. Taxonomic beta diversity was dichotomously regulated by climatic stability and land use: diminishing nestedness in low‐latitude regions while augmenting spatial turnover in high‐latitude regions as latitude increased. For functional beta diversity, climate was identified as an indirect factor influencing historical trait‐pool constraints, whereas land use was identified as a direct factor altering its nestedness component. Phylogenetic beta diversity demonstrated no significant association with contemporary environmental variables. Main Conclusions This study uncovers three facets of macroinvertebrate beta diversity with different latitudinal patterns, highlighting the disparate influences played by climate and land use on these spatial differences as well as the distinct importance of processes causing nestedness and turnover. These insights provide a foundation for latitude‐specific conservation strategies that aim at preserving the macroinvertebrate diversity in rivers.

Recent advances in Pyrazolo[3,4-d]pyrimidine-based dual inhibitors in the treatment of cancers - Hanrui Jiang; Nan Li; Ruosong Qin; Siyu Lin; Xuelian Wang; Chunyan Li; Jiwei Shen; Ye Chen; Ju Liu; Shi Ding (Molecular Diversity, 2025)

Bioaugmentation with Zymomonas mobilis modulates microbial succession and enhances volatile profiles in strong-flavor Daqu fermentation - Hanrui Lin; Linpei Liu; Yong Zhuang; Bo Wu; Junkai Ma; Yiran Ma; Mingxiong He (International Journal of Food Microbiology, 2025)

Bioleaching of Silicon from Fly Ash by Co-culture of Silicate Bacteria and Fungi - Yanzhu Lin; Shida Li; Xuefeng Li; Hanrui Lin; Ningfei Lei; Di Wu; Jin Tong; Hongguan Xie (Water, Air, & Soil Pollution, 2023)

Understanding the different responses from the similarity between displacement and groundwater level time series in Beijing, China - Hanrui Sun; Lin Zhu; Lin Guo; Yong Luo; Dong Du; Ying Sun (Natural Hazards, 2022)